AB0223 ASSESSMENT OF DISEASE ACTIVITY IN SYSTEMIC SCLEROSIS: THE COMPARISON BETWEEN REVISED EUSTAR AND ESCSG ACTIVITY INDEXES. (June 2019) - yalçınkaya, yasemin; Gazel, ümmügülsüm; Tahra, Sema Kaymaz; Aksoy, Aysun; Karabacak, Murat; Kutluğ, Seda; Pehlivan, Ozlem; Alibaz-Oner, Fatma; Atagündüz, Pamir; Inanc, Nevsun; Direskeneli, Haner
Abstract : Background: Assessment of disease activity in systemic sclerosis (SSc) is challenging and usually hard to distinguish from damage or chronicity. Objectives: We aimed to evaluate disease activity by different indexes and compare them in a SSc cohort. Methods: Disease activity was evaluated by revised EUSTAR (European Scleroderma Trials and Research group) and EScSG (European Scleroderma Study Group) activity indexes in 131 SSc patients fullfiling ACR/EULAR classification criteria (2013). The patients with the scores of EUSTAR activity index ≥2.5 or EScSG activity index ≥3 were accepted as having active disease. Results: Demographics, disease characteristics and nailfold video-capillaroscopic (NVC) pattern details were summarised in table-1 . The scores of EUSTAR and EScSG activity indexes were correlated well (r=0.576, p=0.000) and the agreement between two scores for activity was moderate (cohen kappa:0.407). The percentages of SSc patients described as having active disease or not according to two activity indexes were summarised in table-2 . Of the patients, 9.9% had active and 70.9% had inactive disease according to both indexes in this SSc cohort. Twenty -one (for EUSTAR) and 4 patients (for EScSG) were described as active according to one index and not to the other. Revised EUSTAR activity index was found to have 76.5% sensitivity and 81.6% specificity when the activity was defined by EScSG activity index. Conclusion: This SSc cohort predominantly had limited cutanous disease, digital vasculopathy and late scleroderma pattern. Defining active disease was differed in 19% of the patients according to EUSTAR and EScSG activity indexes, former described higher frequency for activity. This difference might be related to validation procedures of these indexes in patients with different predominant stages of SSc disease, content of the index and the features of the cohort. Disclosure of Interests: None declared